Thermoplastics and thermoplastic composites - Biron, Michel (William Andrew, 2013)
This book bridges the technology and business aspects of thermoplastics, providing a guide designed for engineers working in real-world industrial settings. The author explores the criteria for material selection, provides a detailed guide to each family of thermoplastics, and also explains the various processing options for each material type. More than 30 families of thermoplastics are described with information on their advantages and drawbacks, special grades, prices, transformation processes, applications, thermal behaviour, technological properties (tenacity, friction, dimensional stability), durability (ageing, creep, fatigue), chemical and fire behaviour, electrical properties, and joining possibilities. Biron explores the technological properties and economics of the major thermoplastics and reinforced thermoplastics, such as polyethylene, and emerging polymers such as polybenzimidazole, Thermoplastic Elastomers (TPEs) and bioplastics. In the second edition, a new section 'plastics solutions for practical problems' provides over 25 case studies illustrating a wide range of design and production challenges across the spectrum of thermoplastics, from metal and glass replacement solutions, to fire retardant plastics and antimicrobials. In addition, Biron provides major new material on bioplastics and wood plastic composites (WPCs), and fully updated data throughout. Combining materials data, information on processing techniques, and economic aspects (pricing), Biron provides a unique end-to-end approach to the selection and use of materials in the plastics industry and related sectors. . Includes a new section of case studies, illustrating best practice across a wide range of applications and industry sectors. New material on bioplastics and sustainable composites.
Includes index.
Title from publisher's Web site; (ScienceDirect; viewed on Oct. 31, 2012).
Keywords: Thermoplastics.; elektronické knihy; electronic books